2009
DOI: 10.1038/ejhg.2009.98
|View full text |Cite
|
Sign up to set email alerts
|

Association of FGFR2 gene polymorphisms with the risk of breast cancer in population of West Siberia

Abstract: Polymorphisms within intron 2 of the FGFR2 gene have been associated with increased risk of breast cancer (BC) in European and Asian populations. The study by Easton et al reported two FGFR2 SNPs, rs2981582 and rs7895676, to be among those most strongly associated with BC risk. Statistical modeling suggested that rs7895676 was the variant responsible for the association observed in the region. In this work, we studied the association between seven FGFR2 SNPs, including rs2981582 and rs7895676, and BC risk in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
(11 reference statements)
2
13
0
2
Order By: Relevance
“…In this hospitalbased case-control study, we evaluated the association between 6 SNPs (rs2981428C/A, rs11200014G/A, rs2981579C/T, rs1219648A/G, rs2420946C/T, and rs2981582C/T) of the FGFR2 gene and early-onset breast cancer without a family history by genotyping a southeastern Chinese population of 118 such patients and 104 cancerfree controls. among the six SNPs, the SNP of rs2981428C/A (C23794A) is close to the 3' end of the gene, and may regulate gene expression through the modulation of mRNa stability (Boyarskikh et al 2009). Five of these SNPs (rs11200014G/A, rs2981579C/T, rs1219648A/G, rs2420946C/T, and rs2981582C/T) were associated with breast cancer risk in previous studies (Easton et al 2007;Hunter et al 2007).…”
Section: Tohoku University Medical Pressmentioning
confidence: 99%
“…In this hospitalbased case-control study, we evaluated the association between 6 SNPs (rs2981428C/A, rs11200014G/A, rs2981579C/T, rs1219648A/G, rs2420946C/T, and rs2981582C/T) of the FGFR2 gene and early-onset breast cancer without a family history by genotyping a southeastern Chinese population of 118 such patients and 104 cancerfree controls. among the six SNPs, the SNP of rs2981428C/A (C23794A) is close to the 3' end of the gene, and may regulate gene expression through the modulation of mRNa stability (Boyarskikh et al 2009). Five of these SNPs (rs11200014G/A, rs2981579C/T, rs1219648A/G, rs2420946C/T, and rs2981582C/T) were associated with breast cancer risk in previous studies (Easton et al 2007;Hunter et al 2007).…”
Section: Tohoku University Medical Pressmentioning
confidence: 99%
“…Aberrant expression of alternatively spliced isoforms of FGFR2 transforms breast cancer cells by sustained signal transduction [4][5][6][7][8][9]. In recent years, some original publications [10][11][12][13][14][15][16] have reported the role of FGFR2 polymorphism in breast cancer risk. The association is restricted to single nucleotide polymorphisms (SNPs) in the linkage disequilibrium block covering intron 2, in which three polymorphic variants, rs1219648 (A [ G), rs2420946 (C [ T), and rs2981582 (C [ T), have been the research focus in scientific community and have drawn increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Easton et al 1 reported two SNPs, rs2981582 and rs7895676 (at the upstream and downstream boundaries respectively of intron 2), as the most strongly associated and suggested that the latter was most likely to be a causal variant as it showed the strongest association with breast cancer risk. Recently, Boyarskikh et al, 19 studying a West Siberian population, noted that rs2981582 explained association with disease much more strongly than rs7895676. The authors hypothesised that the actual causal variant lies somewhere within the LD block that includes these two SNPs.…”
Section: Discussionmentioning
confidence: 99%